My summer darlings - Cobb, May, 1973- (Berkley, 2022)
"Three lifelong friends plus a dangerous, sexy new stranger in town add up to a scorching summer of manipulation, obsession, and murder, from the acclaimed author of The Hunting Wives. A woman in the forest thinks she's going to die. I know he's coming back for me. Jen Miller, Kittie Spears, and Cynthia Nichols have been friends since childhood. Now approaching forty, their lives have changed, but their insular East Texas town has not. They stay sane by drinking wine in the afternoons, dishing about other women in the neighborhood, and bonding over the heartache of raising ungrateful teens and their own encroaching middle age. Then Will Harding comes to town, moving into one of the neighborhood's grandest homes. Mysterious and charming, he seems like the answer to each woman's prayers. He's a source of fascination for Jen, Kittie, and Cynthia, but none of them are ready for the way Will disrupts their lives. As Will grows closer with each of the women, their fascination twists into obsession, threatening their friendships with each other and their families. When he abruptly pulls away, each woman scrambles to discover the source of his affection. What they'll uncover is far more sinister and deadly than any of them could have ever imagined"--